Assessment of Growth and Development of Representatives under the Conditions of Chestnut Soils - Alexandra V. Semenyutina (Polish Society of Ecological Engineering (PTIE), 2022)
The growth and development of woody plants allow us to reveal the essence of their relationship with the environment. New conditions for growing plants primarily affect growth and development, which is associated with the amount of heat and moisture. The aim of the research is to study the dynamics of growth and development of Gleditsia in new cultivation conditions (chestnut soils of the Volgograd region). In the arid zone of Russia, a comparative analysis of the species of the genus Gleditsia: G. texana, G. cassis, G. triacanthos, growing in the cluster dendrological collections of the Federal Research Center of Agroecology of the Russian Academy of Sciences (cadastre. № 34:34:000000:122, 34:34:060061:10; cadastre no. 34: 36:0000:14:0178). The analysis of long-term phenological observations at various temperature parameters of the environment is carried out. The optimal temperature for the beginning of active growth of shoots, its intensity is revealed. It is established that in the conditions of arid climate of the Volgograd region, species of the genus Gleditsia are characterized by a spring-summer period of shoot growth (from the first decade of May to the third decade of July). Apical shoots start to grow earlier and finish it later than the lateral ones. At the time of cessation of growth in all species, the tops of the shoots dry up together with 2 – 3 leaves. Then comes the process of lignification of young shoots, contributing to their winter resistance in conditions. The period from the beginning of budding to flowering depends on weather conditions (an increase in temperature to 28 °C slows down this process). In hydrologically favorable years, at an average air temperature of 21.5 °C, continuous flowering of plants is observed). The obtained materials are necessary for selection for landscaping, assessment of aesthetic and sanitary-hygienic properties, development and implementation of measures to protect green spaces from pests and diseases. Phenological observations have a huge role for forest reclamation.